Small and micro combined heat and power (CHP) systems : advanced design, performance, materials and applications - Beith, Robert, ....- (Oxford : Woodhead, 2011)
Small and micro combined heat and power (CHP) systems provides a systematic and comprehensive review of the technological and practical developments of small- and micro-CHP systems. Part 1 opens with reviews of small- and micro-CHP systems and their techno-economic and performance assessment, as well as their integration into distributed energy systems and their increasing utilization of biomass fuels. Part 2 focuses on the development of different types of CHP technology, including internal combustion and reciprocating engines, gas turbines and microturbines, Stirling engines, organic Rankine cycle process and fuel cell systems. Heat-activated cooling (i.e. trigeneration) technologies and energy storage systems important to the regional/seasonal viability of this technology round out this section. Finally, Part 3 covers the range of applications of small- and micro-CHP systems, from residential buildings and district heating, to commercial buildings and industrial applications, as well as reviewing the market deployment of this important technology.